Ethnopharmacology and therapeutic potential of Anchusa strigosa: a comprehensive review - Chebaro, Ziad; Badran, Adnan; Maresca, Marc; Baydoun, Elias; Mesmar, Joelle Edward (Frontiers in Pharmacology, 2023)
Anchusa strigosa Banks & Sol. is a rough flowering plant of the Boraginaceae family native to Eastern Mediterranean region that is widely used in traditional herbal medicine, mainly for the treatment of wounds, abdominal pain, and arthritis, to name a few. This article aims to gather knowledge related to the medicinal properties of A. strigosa. Specifically, it summarizes its traditional uses and pharmacological activities in the treatment of various diseases. Moreover, its botanical, ecological, and phytochemical characteristics are also discussed. Research showed that this plant is rich in pyrrolizidine alkaloids, particularly in the leaves. Other bioactive metabolites identified in this plant include flavonoids, phenolic acids, triterpenes, organic acids, and volatile organic compounds. These phytochemicals are responsible for the reported pharmacological properties of A. strigosa, including antimicrobial, antioxidant, anticancer, anti-inflammatory, antiarthritic, gastric protective, antidiabetic, and pro-wound healing. This warrants further investigation into the molecular mechanism of action behind the observed effects to elucidate its therapeutic potential. Nevertheless, more research on this plant is needed to ensure its efficacy and safety. This is a provisional file, not the final typeset article development of many drugs either directly or indirectly by using the core structure of natural bioactive metabolites as scaffolds. For example, morphine, which is found in Papaver somniferum, was the first natural product introduced and used as a therapeutic drug in 1826. And aspirin was developed as a semi-synthetic drug in 1899 to treat pain, fever, and inflammation, as a derivative of salicilin from Salix alba. Other examples of plant-derived drugs include Paclitaxel from Taxus brevifolia, which is chemotherapeutic agent used for the treatment of various cancers, and Artemisinin from Artemisia annua, used for the treatment of multidrug-resistant malaria, to name a few.Anchusa is a major genus of rough flowering plants that belongs to the Boraginaceae family, with around 34 accepted species growing mainly in a temperate biome. It is native to Europe, the